Lightweight HMAC-Based Anti-Linkability Authentication Scheme with Bloom Filter Token Revocation for V2I Network - Lashari, Saima Anwar; Jaber, Ebtesam Sabree; Al-Shareeda, Mahmood A.; Almaiah, Mohammed Amin (Informatica, 2025)
In this paper, we present a lightweight privacy-preserving authentication scheme for vehicle-toinfrastructure (V2I) communications with the following features: (1) resistance against linkability and (2) forward secrecy. The suggested solution is designed as a 4-phase protocol: pseudonym set-up, token-based authentication, session concealment and pseudonym-token refresh. Using symmetric HMAC operations and Bloom filter based revocation, the scheme provides a secure session management and an efficient revocation without computational overhead of PKI. We formally modeled and verified the proposed scheme by using AVISPA which confirmed resistance against replay, impersonation and man-in-the-middle attacks as well as mutual authentication and session unlinkability. The lightness of the protocol has been verified by comprehensive simulations, with computation time reduced by up to 35% and communication overhead saved by up to 22% versus the state-of-the-art works OTAuth and ECA-VFog. These results illustrate the adaptability of our protocol into a latency-sensitive and resource-constrained vehicular environment.